134 Group-based cognitive behavioural approach to managing fatigue in multiple sclerosis is effective: a multi-centre parallel arm randomised controlled trial. Issue 3 (9th February 2012) - Thomas, S; Thomas, P W; Kersten, P; Jones, R; Green, C; Nock, A; Slingsby, V; Hillier, C E M; Galvin, K; Baker, R
Abstract : Aim: Fatigue is one of the most commonly reported symptoms of MS. This trial evaluates the clinical effectiveness of a group-based fatigue management intervention for people with MS. Study design: Pragmatic multi-centre parallel arm randomised controlled trial of a group-based fatigue management intervention compared to current local practice. The six session intervention blends cognitive behavioural and energy effectiveness approaches to managing fatigue. Participants were adults with MS and significant fatigue levels. Primary outcomes were self-reported fatigue severity (Fatigue Assessment Instrument), self-efficacy (MS—Fatigue Self-Efficacy scale) and disease-specific quality of life (MS Impact Scale) measured before, and 1 and 4 months after, the intervention. Results: 164 people with MS randomised across three centres in England. Primary outcome data were available on 146 (89%), and 74% of participants attended at least five sessions. Mean self-efficacy was higher in the fatigue management intervention arm at 1 month (standardised effect size (ES) 0.54, p=0.001) and 4 months (ES 0.36, p=0.05), and mean fatigue severity was lower at 4 months (ES 0.35, p=0.01). There were no statistically significant improvements in the quality of life scale. The mean cost of the intervention was approximately £450 per person. Conclusion: The results show that the intervention improves self-efficacy and reduces fatigue severity in people with MS. The intervention is novel in that it blends cognitive behavioural and energy effectiveness approaches to managing fatigue, and has been designed so that it can be delivered by those health professionals who already work with people with MS.